Detection of Y chromosomal material in patients with a 45,X karyotype by PCR method - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP (TOHOKU UNIV MEDICAL PRESS, 2007)
A 45,X karyotype is one of the common chromosomal abnormalities characterized by short stature, lack of development of secondary sexual characteristics, webbed neck and cubitus valgus. This phenotype was described by Turner in 1938 and was called Turner syndrome (TS). About 40-60% of the patients with TS phenotype have a 45,X karyotype, the rest either have a structurally abnormal X or Y chromosome or mosaicism with a second cell line. Determination of Y chromosome derivatives in patients with a 45,X karyotype is important for the management of these patients due to increased risk of gonadoblastoma. Low level mosaicisim of Y chromosome may be missed by cytogenetic methods. The aim of our study is to analyze cryptic Y chromosome derivatives using Y specific sequences in 40 Turkish patients with a pure 45,X karyotype. Fourteen different Y specific sequences along the Y chromosome were selected for the detection of cryptic Y chromosome material by PCR analysis. The present study demonstrated that 2 patients with a 45,X karyotype (5%) have Y specific sequences except sex releated region Y (SRY). One of them had displayed enhanced virilisation whereas other showed no virilisation. In conclusion, it has been found by PCR analysis that 5% of patients with a 45,X karyotype have Y chromosome sequences in the absence of any marker chromosome by cytogenetic analysis. The data also suggest that the patients with a 45,X karyotype should be analyzed for the presence of Y chromosome derivatives by sensitive methods, such as PCR, in order to calculate the future risk of developing gonadoblastoma.
Keywords: 45,X karyotype; Y sequences; PCR; gonadoblastoma; virilisation; ULLRICH-TURNER-SYNDROME; DYSGENETIC GONADS; GONADOBLASTOMA; SEQUENCES; MOSAICISM; ANEUPLOIDY; FREQUENCY; TESTIS; CELLS; GENE